Formative Principles and Methods of Modeling in Fashion Design - Gasem, Amina (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The main objective of the study is to analyze the key principles of the formative process in fashion design and the methods of their application in the educational training of fashion designers. Using the examples of works created by the author and by students of the Kharkiv State Academy of Design and Arts within the educational and professional program Fashion Design in the discipline Shape Formation (by specialization), the article presents approaches to organizing shape in the modeling process and outlines the stages of its transformation. The author demonstrates techniques for applying paper plastics and shows its influence on the formative tools of design, as well as the sequential logic of creating layouts from paper and materials with different plastic properties. Artistic and compositional means of form creation are systematized, forming the basis of a methodology for the educational process. This methodology serves as preparatory training for more complex disciplines such as Designing Complex Forms of Clothing and Modeling the Plastic Form of a Costume. The formative means are substantiated as a creative factor in the educational process at the initial stage of designing clothing models of different levels of complexity. The scientific novelty of the study lies in the systematization of formative principles and in the comprehensive consideration of the three-dimensional interpretation of clothing models made of paper and other materials directly on a mannequin. This is viewed as a foundation for a creative approach and self-expression in modern design. The materials presented in the article are of clear practical value and are primarily intended for use in the professional training of fashion designers and stylists. At the same time, they may also prove useful for preparing scientific studies on related topics. The results of the research can be applied to the development of modern clothing collections both in academic training and in professional practice.